DOMINATION OF THE INCLUSION OF THEO VAN LEUWEEN IN TRIBUN JABAR NEWSPAPER “SEKARANG RUMAH SAYA HARUM TAK BAU PESING LAGI” - Ratih Sapdiani; Alfian Purnama; Teti Sobari (IKIP Siliwangi, 2019)
AbstractTheo Van Leeuwen's critical discourse analysis focuses on two things, namely exclusion and inclusion. The discourse raised in this study is in the Tribun Jabar Newspaper, with the title Sekarang Rumah Saya Harum Tak Bau Pesing Lagi. This study aims to: 1) frame the analysis of the discourse of Sekarang Rumah Saya Harum Tak Bau Pesing Lagi, and 2) describe the results of the discourse analysis with Theo Van Leeuwen's critical discourse analysis model which focuses on exclusion and inclusion. The method used to collect the data is descriptive qualitative method. The results of this study indicate that the exclusion model carried by Van Leeuwen is not very obvious both passivation, nominalization, and clauses. However, the two figures that were actually the subject of the title were not discussed in detail. Meanwhile, in inclusion, there are sentences that show differentiation, differentiation, and assimilation.